(untitled) (Sebha University Conference Proceedings, 2025)
This paper presents the design and implementation of an automated faculty attendance system using QR code technology, integrated with Sebha University’s Student Information System (SIS). The system addresses inefficiencies in manual attendance tracking during examinations by leveraging a web-based platform built with PHP and CodeIgniter, along with a MySQL relational database. Key features include real-time QR-based attendance logging for invigilators, automated conflict detection—such as duplicate entries—and seamless integration with exam scheduling data from SIS. Testing demonstrated 100% accuracy in attendance recording, and the system’s scalable architecture makes it adaptable for use at other universities.